Large for gestational age and macrosomia in singletons born after frozen/thawed embryo transfer (FET) in assisted reproductive technology (ART). Issue 8 (1st May 2018) - Berntsen, Sine; Pinborg, Anja
Abstract : Increase in success rates with frozen embryo transfer (FET) and reduced risk of ovarian hyperstimulation syndrome (OHSS) and multiple pregnancies has lead to a steady rise in FET. Further, FET is associated with lower risk of prematurity and low birth weight in singletons, when compared with fresh transfer. However, there is a growing concern of increased risk of large for gestational (LGA) and/or macrosomic children after FET. Macrosomic/LGA births have a higher risk of cesarean section, fetal hypoxia and stillbirth. Improvements in cryopreservation techniques indicate that FET is a trend expected to continue and a freeze‐all policy has lately been introduced. With this review, we wished to evaluate the association between FET and LGA and/or macrosomia. We searched electronic databases on January 12, 2018. Ten studies on LGA and six studies on macrosomia were eligible for meta‐analysis. We found that the risk of LGA in FET was increased 1.5‐fold (AOR = 1.50 95% CI 1.44–1.57 p  < 0.001) compared to fresh cycles and 1.3‐fold (AOR = 1.31 95% CI 1.20–1.43 p  < 0.001) compared to natural conception (NC). Similarly we found a 1.7‐fold increased risk of macrosomia in FET compared to fresh transfer (AOR = 1.71 95% CI 1.59–1.83 p  < 0.001) and a 1.4‐fold increased risk compared to NC (AOR = 1.42 95% CI 1.17–1.71 p  < 0.001). Whether the increased risk of LGA and macrosomia is associated with higher long‐term health risks remains unknown. Future studies should explore epigenetics modifications in children born after FET and predictors of long‐term diseases need to be examined further with longitudinal studies.